2019
DOI: 10.17576/jsm-2019-4803-19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Treatment on Structural Characterisation, Thermal Degradation and Water Absorption Ability of Coir Fibre Polymer Composites

Abstract: The alkaline treatment with 5 wt. % sodium hydroxide (NaOH) solution at room temperature for 24 and 48 h was performed on coir fibre. The structural characterisation, thermal degradation and water absorption ability of the untreated and NaOH-treated coir fibre polymer composites have been studied. Scanning electron microscope (SEM) images showed that coir fibres treated with NaOH have rough surface texture and the roughness of the fibre surface becomes significant as the duration of the NaOH treatment increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…This could be due to the carboxyl and acetyl groups in hemicelluloses being soluble or easy to dissolve in aqueous alkali solution, thus causing the peak to disappear. The same phenomenon coincided with previous research which reported that alkali treatment removed hemicellulose [38,39]. The existence of that peak in combination-pretreated wood was correlated with succinic acid impregnation after alkali immersion.…”
Section: Chemical Changes To Densified Wood Under Several Treatment C...supporting
confidence: 91%
See 1 more Smart Citation
“…This could be due to the carboxyl and acetyl groups in hemicelluloses being soluble or easy to dissolve in aqueous alkali solution, thus causing the peak to disappear. The same phenomenon coincided with previous research which reported that alkali treatment removed hemicellulose [38,39]. The existence of that peak in combination-pretreated wood was correlated with succinic acid impregnation after alkali immersion.…”
Section: Chemical Changes To Densified Wood Under Several Treatment C...supporting
confidence: 91%
“…Chen et al [17] added that the shift in wavelength occurs when a 10% concentration is applied. The shift also occurred in alkali-treated coir fibers with 24 h and 48 h of immersion time [38].…”
Section: Chemical Changes To Densified Wood Under Several Treatment C...mentioning
confidence: 76%
“…For the composite with a ratio of 1:1, the main thermal degradation stage occurred at around 250 to 410 • C, whereas for the ratio of 3:1, it happened at 290 to 450 • C. For the ratio of 1:3, the degradation occurred at 250 to 410 • C. On the other hand, for the composite containing alkali-treated fibers at a ratio of 3:1, thermal degradation occurred at a lower temperature at around 245 to 380 • C. From the outcomes, it was evident that alkaline treatment on fiber decreases the thermal degradation of the composites compared to the untreated fiber [122]. According to Yew et al [48], untreated fiber has a larger moisture content than treated fiber, owing to the increased amount of hemicelluloses and lignin, resulting in more moisture absorption in the fibers. When untreated fiber is heated, there is greater weight loss due to the evaporation of moisture.…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Thermoplastic Compositesmentioning
confidence: 96%
“…From the outcomes, it was evident that alkaline treatment on fiber decreases the thermal degradation of the composites compared to the untreated fiber [ 122 ]. According to Yew et al [ 48 ], untreated fiber has a larger moisture content than treated fiber, owing to the increased amount of hemicelluloses and lignin, resulting in more moisture absorption in the fibers. When untreated fiber is heated, there is greater weight loss due to the evaporation of moisture.…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Thermoplastic Compositesmentioning
confidence: 99%
“…After analysis, it was found that the residual weight of raw CSW 11% lower compare to raw CSW. When the treated fibres were subjected to heat, less chars were generated and resulting in lower amount of residual weight [27].…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%